Individual Model of Psychological Health in Educational Process Subjects in Distance Learning Conditions - Akhmedova, Elmira Magomedgadzhievna (2021)
The article examines the problem of studying the individual model of psychological health of the students and employees of the Moscow International Academy (MIA). The goal is to explore the specific characteristics of personal psychological health in MIA students and employees. The implementation of the research program required the researcher to be ready and able to interact in the field of mental and psychological health of the individual, knowledge of age, individual psychological characteristics of the respondents to develop a research program, the ability to conduct psychodiagnostic work, the ability to analyze their own activities in order to optimize it, as well as to be creative. solving the assinged tasks. Authors used the methodology “Individual model of psychological health” by A.V. Kozlov. The method “Individual model of psychological health” was developed in 2014 in the course of psychosemantic analysis of the concept by students of the phenomenon of psychological health. Based on the data acquired, it can be concluded that the hypothesis on the influence of self-isolation on the model of psychological health in various age groups is partially confirmed as older study participants face difficulties with life prospects and experience stress when planning their future. Students also demonstrate low development levels in some components of the model explained by the general level of personality development in the intellectual and spiritual aspects.